Motivations behind Gen Z’s news sharing on social media: a PLS-SEM study in Vietnam - Hai, Le Dinh; Xiong, Xiao Yan (Frontiers in Psychology, 2025)
This study investigates the determinants of news-sharing behavior among Generation Z users on social media in Vietnam by integrating three theoretical frameworks: Newsworthiness Theory, Uses and Gratifications Theory (U&G), and the Theory of Planned Behavior (TPB). A structural equation modeling approach (PLS-SEM) was employed to examine the relationships between perceived news value (social significance, audience relevance), user gratifications (information seeking, socializing, status seeking, entertainment, and pass-time), and psychological drivers such as Fear of Missing Out (FoMO). Data were collected from a stratified random sample of 1.224 high school and university students across six socio-economic regions. The results reveal that social significance, audience relevance, and most gratification-based motivations—excluding pass-time—significantly influence the intention to share news. FoMO was found to positively moderate the impact of information seeking and status seeking on sharing intention. Furthermore, intention to share news significantly predicted actual news-sharing behavior, with inattention to news credibility acting as a mediating factor. The findings underscore the importance of both content attributes and user psychology in shaping digital news sharing among youth. Practical implications are discussed for media organizations aiming to enhance engagement and credibility in the digital era.